Investigation on the algorithm efficiency of generating the interlocking control table using the compositional approach - Ibnazia, Mahtab (My University, 2022)
The control table is the most essential document that specifies all the safe movements of the trains on the railway track and prevents any possible conflicting movement of trains on the railway track. The work presented extends and contributes to research into train authorisation systems which are also known as railway signalling systems. It focuses on the automatic generation of the control table using a compositional approach. Although previous work in this area has produced various conventional approaches to generate and validate the control table automatically, there has not been sufficient investigation into generation of control tables using the compositional approach. Conventionally the control table is generated by linking the railway signalling elements together according to their geographical position in the station layout and developing algorithms that produce the conditions of the control table. In the compositional approach the large station is divided in sub-sections and algorithms are developed to produce the conditions of the control table using these sub-sections. In the research presented, the complexity of the algorithm on generating the control table applying the compositional approach is analysed. Software algorithms are developed for both the approaches, namely the conventional approach and the compositional approach. These algorithms are applied on a number of station layouts by gradually increasing the size of the station layouts. It is transpired through the experimental results that generating the control tables using compositional approach is approximately 48% more efficient than the conventional approach for the station layouts that is used in this research. Hence it can be envisaged that the control table generating program using the compositional approach will become more efficient as the larger and more complex station layouts are used. This research work contributes a unique and valuable insight into the control table generation in railway signalling that also combines the knowledge of software development which is in accordance with demand of the modern signalling technologies.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and Built Environment, School of Electrical and Information Engineering, University of Witwatersrand, Johannesburg, 2022